Synchronous colorectal adenomas - Radovanović-Dinić Biljana; Nagorni Aleksandar; Stamenković Ivanka; Zlatić Aleksandar (Srpski Arhiv za Celokupno Lekarstvo, 2010)
Introduction Colorectal adenomas which are discovered simultaneously or 6 months after the diagnosis of primary adenoma or colorectal cancer (CRC) are called synchronous adenomas. The presence of synchronous adenomas increases the probability of adenomas with severe dysplasia as well as CRC. Objective The aim of the study is to show the characteristics of synchronous colorectal adenomas and to present the relation between the index rectal adenoma and the proximal synchronous tumours. Methods The research included 114 synchronous colorectal adenomas diagnosed in 58 patients. Total colonoscopy was performed on all patients. Results The largest number of patients had two adenomas (p<0.001). Synchronous adenomas were more often diagnosed in men older than 50 (p<0.001). The largest number of adenomas was localized in the sigma (52 patients, 43.0%) (p<0.001). The biggest number of tumours was localized in the combination of rectum-sigma segments (p<0.001). There were 31 (25.6%) synchronous, that is index tumours of the rectum and 90 (74.4%) the so-called proximal synchronous tumours of the proximal part of the colon. In 33 (56.9%) patients, who did not have the index tumour, the prevalence of proximal synchronous tumours was the highest (57.0%) (p<0.001). Conclusion The probability of adenoma multiplication is higher in men, and it increases with age. Beside the fact that synchronous adenomas are more often found distally, a great probability of finding proximal tumours shows that total colonoscopy is the method of choice for the discovery of colorectal tumours. Complete colonoscopic mapping of all colorectal adenomas and their removal prevents the development of metachronous, overlooked benign CRC already present at the moment of initial diagnostics that could be the cause of the development of metachronous CRC. .